Capital subsidies versus labour subsidies: A trade-off between capital and employment? - Alberto Petrucci; Edmund S. Phelps (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper examines the consequences of capital and labour subsidies for employment, capital formation and other macroeconomic variables within an OLG small open economy model of wealth accumulation. Two cases, the neoclassical-equilibrium one and the modern-equilibrium one, have been analysed. We discover that the employment effects of the subsidies studied differ significantly, while whether the subsidy hike is financed by an increase of payroll taxation or a decrease of employment subsidisation is immaterial for the qualitative effects on the macroeconomic system. In the neoclassical-equilibrium theory, a capital subsidy causes a temporary increase in hours worked which vanishes in the new long run, while an increase in labour subsidy has no aggregate effects on the macroeconomic equilibrium. The key finding of the modern-equilibrium case is the existence of a negative relationship between capital formation and employment. Capital subsidies boost investment and aggravate unemployment, while labour subsidies stimulate employment and may depress capital accumulation.
Keywords: E24; J32; J38; 330; Capital subsidy; employment subsidy; structural unemployment; wealth accumulation; Subvention; Lohnsubvention; Beschäftigung; Beschäftigungspolitik; Kleine offene Volkswirtschaft; Theorie